The Impact of Race and Partner Status on Patterns of Care and Survival in Young Women With Early-Stage Cervical Cancer. Issue 3 (1st March 2013) - Grover, Surbhi; Showalter, Shayna; Kraft, Kate H.; Suneja, Gita; Lin, Lilie
Abstract : Objectives: Although outcomes for surgery versus radiotherapy (RT) for stage IB patients are similar, young women are often preferentially treated with surgery rather than RT. Adjuvant RT is indicated for high-risk patients after surgery. Our goal was to study the impact of race and partner status on patterns of care of young women with stage I cervical cancer. Methods: We identified a cohort of 6586 women, aged 15 to 39 years, in the Surveillance, Epidemiology and End Results database diagnosed with stage I cervical cancer between 1988 and 2007. Results: In our cohort, 93% (n = 5080) of white women had surgery, and 86.5% (n = 985) of nonwhite women had surgery as primary treatment. On multivariate analysis, higher FIGO (International Federation of Gynecology and Obstetrics) stage (IA2 odds ratio [OR] 3.09 [ P = 0.01]; IB OR, 21.41 [ P < 0.001]), widowed/single (OR, 1.39; P = 0.02), squamous histology (OR, 1.69; P < 0.001), diagnosis during 1993-1997 time period (OR, 1.69; P < 0.001), and nonwhite race (OR, 1.95; P ≤ 0.001) were more likely to receive RT as primary treatment. Of the surgical patients, 15.45% of white women versus 20.4% in the nonwhite women ( P < 0.001) had high-risk disease, and 66% of the white women versus 71% of the nonwhite women received adjuvant RT ( P = 0.136). Race and marital status were not significant predictors of receiving adjuvant RT on multivariate analysis. Predictors of worse overall survival included RT as primary treatment (hazard ratio [HR], 1.89; P < 0.001) and nonwhite race (HR, 1.6; P = 0.001). Marital status was not a significant predictor of overall survival. Race was a significant predictor of survival for women who received surgery as primary treatment (nonwhite HR, 1.93; P < 0.001). Conclusions: Nonwhites are more likely than whites to have RT as primary treatment. This suggests that nonwhite women may have social/cultural barriers impacting their treatment decision making or may have a higher likelihood of other comorbidities that limit their surgical options.